2023
DOI: 10.1007/s10792-023-02809-9
|View full text |Cite
|
Sign up to set email alerts
|

Randomised placebo-controlled clinical trial evaluating the impact of a new visual rehabilitation program on neuroadaptation in patients implanted with trifocal intraocular lenses

Abstract: Purpose To evaluate the efficacy of a new visual training program for improving the visual function in patients implanted with trifocal intraocular lenses (IOLs). Methods Randomised placebo-controlled clinical trial enrolling 60 subjects (age, 47–75 years) undergoing cataract surgery with implantation of trifocal diffractive IOL. Home-based active visual training was prescribed immediately after surgery to all of them (20 sessions, 30 min): 31 subjects usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…It is important to note that the mitigation of these effects typically occurs over time, and this is attributed to neuroadaptation. 25 A study by Asena revealed minimal disparities between the PanOptix and AT LISA tri IOLs regarding the frequency, intensity, or perceptual disturbance of diverse visual symptoms like halos and glare. 26 Similarly, Vargas et al's investigation revealed no statistically significant differentiation between the AT LISA tri and a bifocal IOL.…”
mentioning
confidence: 99%
“…It is important to note that the mitigation of these effects typically occurs over time, and this is attributed to neuroadaptation. 25 A study by Asena revealed minimal disparities between the PanOptix and AT LISA tri IOLs regarding the frequency, intensity, or perceptual disturbance of diverse visual symptoms like halos and glare. 26 Similarly, Vargas et al's investigation revealed no statistically significant differentiation between the AT LISA tri and a bifocal IOL.…”
mentioning
confidence: 99%